Analysis of laundry business model using the business model canvas (BMC) approach - Prapdop Prapdop; Della. O. C. Kalangit; Khairunnis Khairunnis; Amanda Amanda; Ramzy Nanda Achmad (Enrichment : Journal of Management, 2025)
This study examines the business model and financial feasibility of Laundry as a small-scale service business operating in urban areas. This study departs from the problem of how a laundry business can maintain operational sustainability while meeting increasing consumer demand. A mixed method was used by combining qualitative analysis through a business model framework and quantitative analysis through financial evaluation. The results show that all elements of the business model have been implemented effectively, although improvements are still needed in digital marketing and customer relationship management. The financial evaluation shows a positive net present value, an adequate rate of return, a short payback period, and a break-even point that reflects cost management efficiency. These findings indicate that this business is viable and has strong potential for future development. Strengthening digital-based promotion, diversifying revenue, and improving cost control were identified as strategies that could improve long-term sustainability